(untitled) (Docentes 2.0 Journal, 2020)
Since we were born, our whole life is marked by the type and quality of the decisions we make. This determines what our "performance" will be in the achievements and failures obtained. For almost 40 years, with the development of technology, neurosciences have contributed (and continue) several research papers, in which it is shown that "emotion" exceeds "reason" when making a " decision”, whether it is simple or complex. The question and objective of this work is: who teaches us to make decisions? Is it something innate or can it be learned? If you can learn, who is awarded for such responsibility? Today we know that, unfortunately, the Latin American education system and parents are not trained, or do not have the need to teach how to handle "emotions", with those children who will grow up in a highly competitive society, so they have to make decisions that affect your present and your future.